Os mandados constitucionais de criminalização e a obrigatoriedade de proteção da saúde pública brasileira como bem jurídico supraindividual - Resqueti, Laís Berti (2022)
This work presents an analysis of the State's omissions regarding to the confrontation of a legal-criminal issue involving the protection of public health, based on a policy of prevention and reproof for the effective protection of the juridical asset. It demonstrates the duty about the Brazilian Parliament in dealing with some themes whose competence are attributed through criminalization warrants provided in the Federal Constitution and the interference of Criminal Law face to a new forms of criminal activity. As a result, globalization has brought the difficult mission of facing a new stratum of criminality that affects the entire social context, injury or threat of injury, not only social rights, but also the protection of the legal right of life. Therefore, the confrontation of issues that affects the structure of the Democratic State of Law requires that the Criminal Law to adapts to contemporaneity for the granting of quality public health to the population, including the imposition of sanctions at an international level against the politicians and of Parliament, when they omit in their typical function to deal with the issue. In this scenario, still to avoid pandemic episodes, in favor of balance in the effective granting of the human right to health, it is observed that, in fact, the penal rules still seek for the protection of the legal interest in a timely manner, with a classic Criminal Law, and they need effective action so that they can follow the constitutional foundation, but linked to a Human Rights agenda. The research was accomplished based on the deductive method, under bibliographic references, in the light of a constitutional history that forms the protection of public health, which flows into the Federal Constitution of 1988, as well as in compliance with sanitary legislation. It is based on the protection of the juridical asset through the recognition of constitutional criminalization warrants and criminal liability arising from omissions in the concession of public health, which seeks for remember the importance of the themes, their interconnection, in the search for legal certainty for effective protection of the legal life